2017
DOI: 10.1007/s11589-017-0198-z
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of neutron and charged particle fluxes toward earthquake prediction

Abstract: In this paper, we describe a possible method for predicting the earthquakes, which is based on simultaneous recording of the intensity of fluxes of neutrons and charged particles by detectors, commonly used in nuclear physics. These low-energy particles originate from radioactive nuclear processes in the Earth's crust. The variations in the particle flux intensity can be the precursor of the earthquake. A description is given of an electronic installation that records the fluxes of charged particles in the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Maksudov and Zufarov proposed a new method for EQ forecasting, based on simultaneous recording of the intensity of fluxes of low-energy neutrons and charged particles by detectors [4].…”
Section: Introduction mentioning
confidence: 99%
“…Maksudov and Zufarov proposed a new method for EQ forecasting, based on simultaneous recording of the intensity of fluxes of low-energy neutrons and charged particles by detectors [4].…”
Section: Introduction mentioning
confidence: 99%
“…Fu et al found anomalous variations in the gamma-ray counting rate a few days before some local EQs in eastern Taiwan [1]. Maksudov et al proposed a new method for EQ forecasting, based on simultaneous recording of the intensity of fluxes of low-energy neutrons and charged particles by detectors [2].…”
Section: Introductionmentioning
confidence: 99%